Pengaruh Gaya Hidup dan Kelompok Acuan terhadap Keputusan Pembelian Smartphone Merek Samsung Galaxy - Anoraga, Bintang Jalasena; Iriani, Sri Setyo (BISMA (Bisnis dan Manajemen), 2018)
Recently common phenomenon in all walks of life use smartphones, ranging from a young children to an adults. Samsung Galaxy Smartphone shows a magnificent display, there are a lot of choices they give to us, provide fairly complete applications, and it can reflects an up to date metropolitan lifestyle by using it. This research is a conclusive research. Sample who taken as many as 110 people with snowball sampling technique. Measuring instrument which used is enquette, as well as the the data analyzed with multiple linear regression. The research instrument that used was a questionnaire, and multiple linear regression analysis. This study shows the results, that there is a positive effect between lifestyle and reference group on purchasing decisions towards purchasing decisions Smartphone Samsung Galaxy simultaneously and the dominant effect is the lifestyle variables followed by variable virtual community.